Espinosa, el último capitán de la Vuelta al Mundo: By TOMÁS MAZÓN SERRANO. Madrid: Ediciones Encuentro, 2022. 302 pp., €22.00 (PB) / €9.99 (ebook). ISBN 978-84-13-39113-7. - Robles Macías, Luis A. (Terrae Incognitae, 2022)
Mazón proves beyond doubt that Espinosa lived until at least 1545. Espinosa managed to lead his two surviving ships - the I Trinidad i and the I Victoria i - to Tidore Island, one of the Moluccas. Espinosa was involved in the Spice Islands project since 1518, when Ferdinand Magellan, Rui Faleiro, and Cristóbal de Haro presented it to Charles I, the new king of Castile.